2019
DOI: 10.2139/ssrn.3401539
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning With Kernels for Portfolio Valuation and Risk Management

Abstract: We introduce a statistical simulation method for dynamic portfolio valuation and risk management building on machine learning with kernels. We learn the dynamic value process of a portfolio from a finite sample of its terminal cumulative cash flow. The learned value process is given in closed form thanks to a suitable choice of the kernel. We develop an asymptotic theory and prove convergence and a central limit theorem. We derive dimension-free sample error bounds and concentration inequalities. Numerical exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 63 publications
0
12
0
Order By: Relevance
“…Our contributions are two-fold: 1. on the theoretical side: (i) we compute analytically the mean embedding for various target distribution -kernel pairs (Section 3.1). (ii) We show (Theorem 3.4) that such analytical knowledge leads to better concentration properties of MMD estimators, (iii) extend the result to the case of unbounded kernels (Theorem 3.5; recently motivated in finance for instance by [5]), and (iv) present minimax lower bounds (Theorem 3.6). 2. on the practical front: we demonstrate that the flexibility of considered measures result in more efficient portfolios in terms of skewness and kurtosis (Section 4-5), which provides a novel application of these divergence measures.…”
Section: Introduction Portfolio Optimizationmentioning
confidence: 61%
See 3 more Smart Citations
“…Our contributions are two-fold: 1. on the theoretical side: (i) we compute analytically the mean embedding for various target distribution -kernel pairs (Section 3.1). (ii) We show (Theorem 3.4) that such analytical knowledge leads to better concentration properties of MMD estimators, (iii) extend the result to the case of unbounded kernels (Theorem 3.5; recently motivated in finance for instance by [5]), and (iv) present minimax lower bounds (Theorem 3.6). 2. on the practical front: we demonstrate that the flexibility of considered measures result in more efficient portfolios in terms of skewness and kurtosis (Section 4-5), which provides a novel application of these divergence measures.…”
Section: Introduction Portfolio Optimizationmentioning
confidence: 61%
“…We showed that prior knowledge available on target distribution leads to analytical forms for the mean embedding (Lemma 3.1 and Lemma 3.2) and improved MMD concentration properties for bounded kernels (Theorem 3.4). Motivated by recent financial studies relying on unbounded kernels [5], using the Burkholder inequality we proved that the 1/ √ N rate (with N denoting the sample size) of MMD estimators can be extended to unbounded kernels (Theorem 3.5); we illustrated the idea for the exponential kernel. We showed matching minimax lower bounds (Theorem 3.6) under slightly more restrictive conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our method is different as it learns the entire value process V in one go, as opposed to any method relying on nested Monte Carlo simulation, which estimates V t for one fixed t at a time. Our method shares some similarities with the kernel-based method in our previous paper [Boudabsa and Filipović, 2022]. There we applied kernel ridge regression to derive a closed-form estimator of the value process V .…”
Section: Introductionmentioning
confidence: 99%